Principal Leadership Strategy in Forming Student Character in the era of disruption 5 - Nashiruddin Cholid; Rokimin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to know and examine the role of the principal in developing student character in Darunnajah Islamic Boarding School. The method in this study is using comprehensive qualitative data, interviews, observations, and document analysis are used as research methods. As a spiritual leader, the principal at Darunnajah Islamic Boarding School plays a very important role. In addition to coordinating religious activities, they also serve as spiritual and moral role models for students. The headmaster also plays an active role in the formulation of a comprehensive character development program that covers spiritual, moral, and ethical dimensions. It also reveals the importance of collaboration between principals, educators, and parents in the process of developing student character. And also Creating an educational environment that fosters the moral and spiritual growth of students requires minimal open dialogue and cooperation in the process of designing a curriculum with character.